Sistem Informasi Pemesanan Lapangan Futsal Secara Real Time Berbasis Web - Bagus Prayogo (Melek IT : Information Technology Journal, 2019)
Futsal became one of the popular sport today and in the community especially Indonesia one of them children, adolescents, and of course adults. The number of futsal teams that are formed shows that this sport is very fun for everyone, but in this day and age there is still place for futsal field booking is still a conventional booking such as a one-on-one meeting, telephone appointments, writing on paper ordering, and so forth. For that in this final task make a futsal field booking information system in real time web based in Barkla futsal field which is still manual for ordering. The purpose of making this system can help field owners and field officers futsal for scheduling arrangements can be done on a web basis by utilizing the Internet network that has been growing rapidly at this time.